Prevalence of skin lesions in patients with diabetes in Iran: a systematic review and meta-analysis - Sobhiyeh, Mohammad Reza; Mohamadi, Masoud; Khatony, Alireza (Dermatology Review/Przegląd Dermatologiczny, 2020)
Diabetes is one of the most common chronic meta- bolic diseases [1]. According to a prediction by the World Health Organization, the number of diabetic patients in 2025 will amount to 333 million adults. Meanwhile, predictions suggest that 4.4% of citizens worldwide will have diabetes in 2030 [2].